THE IMPACT OF TAXATION CHANGES ON THE GAMBLING MACHINE MARKET - MIAO, RUNZE (2016)
This paper focuses on the relationship between the shift of tax and merger activities in the gambling markEet. I propose to use the theory of FCF and EV to study whether gambling firms are more profitable under the case of GPT than AMLD. If integrated firms were levied by the proposed tax policy which just changes the levying period for merged firms, new enterprises would benefit a lot.